(untitled) (Dialogos, 2018)
Resumo. No Sul do antigo Estado de Mato Grosso (correspondente, grosso modo, ao atual Mato Grosso do Sul) registram-se, desde fins do século XIX, reivindicações de autonomia em face das oligarquias ditas “nortistas”. Este trabalho analisa documentos dos divisionistas sulistas de meados da década de 1930 para sugerir que neles se esboça a construção de uma identidade especificamente sul-mato-grossense, como resposta Ã “identidade mato-grossense” elaborada pelos “nortistas”. Busca-se também mostrar que, tendo logrado ascender ao poder estadual, as elites sulistas praticamente abandonaram as idéias de divisão e de construção da “identidade sul-mato-grossense”. Critica-se, enfim, a retomada dessa construção no período seguinte Ã divisão do Estado, ocorrida em 1977. Abstract. In the southern portion of former Mato Grosso State (i.e. the portion which roughly constitutes, in present days, the Mato Grosso do Sul State), claims for autonomy before the so named “northern” oligarchies have been made since the late nineteen century. By analysing documents issued in the mid-1930s by southern divisionistas (those who supported the proposition of partitioning the state’s territory), this paper suggests that in suchlike documents the construction of a specifically southern (it means, sul-mato-grossense) identity is outlined, in reply to the “official” (it means, mato-grossense) identity built-up by the “northerners”. The article also intends to demonstrate that the southern elites virtually deserted those ideas of state partition and sul-mato-grossense identity construction after getting to rise to the state’s political power. Finally, the paper criticizes the resumption of aforesaid construction after the effective division of the state occurred in 1977.